Problem based learning: a model in teaching English at junior high school - Isrokijah Isrokijah (Universitas Islam Malang, 2020)
Problem Based Learning (PBL) is one of teaching models required in Curriculum 2013. However, not many teachers apply it in teaching English. This happens because of their lack of knowledge about PBL and how to apply it in the class. This article aims at elaborating how to implement problem based learning (PBL) as an effective model in teaching and learning English at junior high school. By knowing how to apply PBL in the classroom it is hoped that the teachers will be motivated to use PBL in their teaching English, PBL increases students' motivation in learning, their ability to work independently and collaboratively with others, and their problem solving skills in order that the English learning objectives can be achieved.